Hubungan Motivasi Berprestasi, Prilaku Kepemimpinan Kepala Sekolah dan Etos Kerja dengan Kinerja Guru - Putra, Cok Agus Ady; Yudana, Made; Natajaya, Nyoman (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2017)
This study aimed to determine: (1) the relationship between achievement motivation with teacher performance, (2) the relationship between principal leadership behaviors with teacher performance, (3) the relationship between the performance of the teachersÂ  work ethic, (4) simultaneous relationship between achievement motivation, school leadership and work ethic with the performance of. This study was designed with a correlational design ex-post facto by using a quantitative approach.The study population wasÂ  all teachers in SMA N 1 Kubutambahan. The sample retrieval technique using census study with the number 47. Data were collected by questionnaires. Data were analyzed by multiple regression and partial analysis. The results showed that: (1) there is a significant contribution to the achievement motivation with teacher, (2) there is a significant contribution between principal leadership behaviors with teacher performance, (3) there is a significant contribution to the work ethos of teacher performance, (4) there is a significant contribution between achievement motivation, school leadership behavior, and work ethos simultaneously with the performance of teachers